Remote sensing for proactive geotechnical asset management of England's Strategic Roads. Issue 4 (1st August 2018) - Ní Bhreasail, Áine; Pritchard, Oliver; Carluccio, Savina; Manning, Jason; Daly, Tony; Merritt, Andrew; Codd, James
Abstract : Highways England operates, maintains and improves England's Strategic Road Network (SRN), which has a diverse asset base. Well-maintained geotechnical assets are key to a safe and smooth-running SRN, and failure of these assets can lead to delays, resulting in significant economic impacts. This paper reviews available remote sensing techniques to understand their potential application for proactively managing Highways England's geotechnical assets. The integration of remote sensing into Highways England's established asset-management processes is discussed. The conclusions suggest that recent technological advances bear promise for a more systematic and widespread application of remote sensing for geotechnical asset management, alongside cross-asset applications, ensuring greater efficiencies. When used alongside other complementary monitoring methods, remote sensing contributes towards improving safety and asset knowledge and a reduced need for physical asset inspections. Specific implementation challenges include the diversity of required scales and techniques, procurement across asset groups and data management and analysis. However, engineers are equipped to overcome these challenges and exploit the potential of remote sensing to ensure a safe, resilient and efficient SRN ultimately.